Types of metaphors and the usage of them in literary texts (Eurasian Scientific Herald, 2023)
This article deals with metaphor in terms of its types and usage in literature. Particular attention is paid to the analysis of use of metaphors in the literary texts. It also provides several examples of metaphors in different writers’ works with classifications